The production and application of riceblock in construction - Hanafi, Zulkifli (2008)

(untitled)
Blocks made from a mixture of cement and agro-waste material such as rice husk can be a new source of alternative construction material in Malaysia for the low income group. The block is light and allow for faster construction which do not use plaster, concrete beam or column but depend on the unique system of dry bonding and interlocking connecting system. In this experimental building system, the main focus is the production of sample block of building material using rice husk and the construction system using dry bonding and interlocking block for house construction. The new block is called the ‘RICEBLOCK’ is a quick, economical and lightweight block for a fast house construction.